Regulatory Policy of Tax Revenues Efficiency Assurance as the Dominant of State Economic Security - Abramova A., Alla Chub A., Kotelevets D., Lozychenko O., Zaichenko K., Popov O. (International Journal of Sustainable Development and Planning, 2022)
The scientific research is devoted to the development of methodological proposals for assessing the effectiveness of tax revenues of the countries of Eastern Europe through the system of economic indicators, the presentation of measures of the regulatory impact of increasing tax revenues in the future and strengthening the economic security of the countries. The methodological basis of the study is a comprehensive approach, thanks to which the tasks and tools of the regulatory policy are established through the prism of the components of tax security of Eastern European countries. The methodological toolkit for assessing the effectiveness of tax revenues in the system of regulatory policy in the direction of guaranteeing the economic security of the state provided for the following stages: collection of economic data, selection of analysis indicators, assessment methods and determination of the system of stimulating and destructive factors influencing the volume of tax payments. Having carried out the analysis, the author's vision of priority tasks and tools of regulatory influence on tax revenues with the aim of increasing the level of economic security of Eastern European countries is presented.
Keywords: economic security, tax security, tax revenues, tax risks, regulatory policy, regulatory tools